Uma visita nunca é só uma visita: receptividade, política e amizade na comunidade quilombola Malhadinha - TO - Alves, Daniella Santos (2023)
This research is the result of the ethnographic immersion carried out in the Remanescente de Quilombo Malhadinha Community, located in the rural area on the border of the municipalities of Brejinho de Nazaré and Porto Nacional, in the State of Tocantins. The objective of this work is to show the constitution and modulations of receptivity – native category – in the daily life of the residents, but also when directed to the different others that appear in their relationships, noting its different uses when it is inflected in the face of conflicts and /or friendships. These modulations indicate the way in which the malhadenses control, approach and/or repel those who enter there. I present, therefore, the thesis of a synthesis of opposites, control and affection: that is, there is a double face in receiving well, constituted by actions that include, at the same time, making friends – lasting bonds of affection –, but which do not cease to on the other hand, asking visitors about the objectives that led or led them there, which makes the reception also marked by a certain amount of control and vigilance. In this sense, receptivity seems to be the way of not only ordering everyday life among the residents of Malhadinha, but also the way of carrying out politics specific to this quilombola community, considering that the reasons behind the arrivals and presence of foreigners are always involved in games of interests, negotiations, hierarchies, knowledge and power.